Joyful And Meaningful Learning In Mathematics Classroom Through Internet Activities - Sitti Maesuri Patahuddin (Southeast Asian Mathematics Education Journal, 2013)
This paper arises from the author experiences over the last eight years with regards to investigating how the Internet could be used as a tool for mathematics learning, mathematics teaching as well as for professional development. This paper illustrates three main categories of the potential of the Internet for learning: the Internet for information, the Internet for communication, the Internet for collaboration, followed by a description on how the use of the Internet could make learning mathematics interesting and meaningfully. Lastly, through the use of a case study and my experiences working with group of students using the Internet, I argue that the success of integrating the Internet into mathematics teaching and learning depends very much on teachers’ knowledge and their philosophical beliefs about learning and teaching, learners, mathematics, and technology.